MiR-526b-3p enhances sensitivity of head and neck squamous cell carcinoma cells to radiotherapy via suppressing exosomal LAMP3-mediated autophagy - Huixiang Lu; Junnian Zhou; Xiaojun Li; Xiaoqin Han; Shuping Ma; Chunlan Feng (Taylor & Francis Group, 2023)
Lysosomal associated membrane protein 3 (LAMP3) has been reported to be a tumour promoter in multiple cancer types by modulating tumour cell autophagy. However, the potential mechanism of LAMP3 in radio-resistance of head and neck squamous cell carcinoma (HNSCC) remains unknown. Therefore, our current study aims to detect the impacts of LAMP3 on the resistance of HNSCC cells to radiotherapy and meanwhile explore its functional mechanism. Through RT-Qpcr examination, LAMP3 expression was identified to be expressed at a significantly high level in irradiation-resistant HNSCC cell lines compared with irradiation-sensitive HNSCC cell lines. Functional assays including CCK-8, colony formation and Transwell assays demonstrated that LAMP3 enhanced the radio-resistance through inducing autophagy to promote HNSCC cell growth. Furthermore, irradiation-resistant HNSCC cells could transfer exosomal LAMP3 to elevate LAMP3 expression in irradiation-sensitive HNSCC cells. Mechanistically, microRNA (miRNA) miR-526b-3p could inhibit LAMP3 expression so as to strengthen sensitivity of HNSCC cells to radiotherapy. In a word, exosomal LAMP3 expression promoted radioresistance of HNSCC cells via inducing autophagy, while this effect could be suppressed by miR-526b-3p in a targeted manner.